Quality Evaluation of the IZAT Application Based on ISO 25010 an PLTU Tembilahan - A. Rukib; Fitri Yunita; Bayu Rianto (Ali Institute of Research and Publication, 2026)
The Zero Accident Assistant (IZAT) application is a mobile-based system developed to support occupational safety management at PLTU Tembilahan, Indragiri Hilir Regency. The research gap identified in this study stems from the absence of systematic and standardized software quality evaluation for occupational safety applications in the power generation sector, particularly using the ISO 25010 standard. Although this application has been operationally deployed, no standardized quality testing has been conducted, making it difficult to systematically identify potential weaknesses. The novelty of this study lies in the comprehensive application of ISO 25010 combined with technical testing tools (OWASP ZAP and GTmetrix) in the industrial occupational safety domain — a methodological combination not previously found in the literature. This study aims to evaluate the quality of the IZAT Application using the ISO 25010 standard, covering eight quality characteristics: functional suitability, performance efficiency, usability, reliability, security, maintainability, portability, and compatibility. The method used is structured questionnaire-based testing and technical testing using automated tools. Respondents consisted of 35 active users selected through purposive sampling and 5 application developers. The results showed that the IZAT application achieved an overall average quality score of 84.76%, classified as